INDONESIA’S REGIONAL ANTI-CORRUPTION COURTS: SHOULD THEY BE ABOLISHED? - Butt, Simon (Indonesia Law Review, 2012)
Indonesia’s regional anti-corruption courts have been criticised in recent times for perceived impropriety and for acquitting defendants. Senior jurists and politicians have called for these courts to be abolished or recentralised. This article suggests that neither abolition nor recentralisation is prudent and that these criticisms might not be supported by available case statistics. In any event, this article argues, acquittal rates are very poor indicators of judicial performance. Indeed, acquittals might be legally correct, or even necessary, in some cases. More resources should be allocated to these courts, and to the Corruption Eradication Commission so that it can investigate and prosecute more cases in Indonesia’s regions